Glycerol Monolaurate Affects Growth, Amino Acid Profile, Antioxidant Capacity, Nutrient Apparent Digestibility, and Histological Morphology of Hepatopancreas in Juvenile Pacific White Shrimp (Litopenaeus vannamei) - Sami Ullah; Bingge Liu; Yunyun Zheng; Hongbo Guo; Yarui Yang; Muhammad Ijaz Ahmad; Siyu Lv; Shijie Deng; Minjie Zhao; Fengqin Feng (Fishes)
An eight-week feeding trial was conducted to evaluate the effects of dietary supplementation with glycerol monolaurate (GML) on Pacific white shrimp (Litopenaeus vannamei). A basal diet was formulated containing 100 g fish meal, while four additional GML-supplemented diets were prepared: GML1 (0.25 g), GML2 (0.50 g), GML3 (0.75 g), and GML4 (1.00 g). Each diet was given to triplicate tanks containing 50 shrimp, each weighing 1.67 ± 0.25 g. GML2 supplementation enhanced the final body weight, weight gain, condition factor, specific growth rate, and viscerosomatic index of the shrimp compared to the other diets (p < 0.05). The whole-body amino acid profile was significantly high in the GML3 group. The antioxidant and immune indicators in the serum, like total protein, triglyceride, and aspartate aminotransferase, were significantly high in the GML2-supplemented group. The immune and antioxidant indicators in the hepatopancreas of the shrimp, like total protein, triglyceride, total cholesterol, and complement protein 3, were significantly high in the GML2 group. However, the malondialdehyde in their livers and serum were significantly high in the control group. Digestive enzymes were significantly high in the GML2 group. In conclusion, this study confirms that GML may benefit the health of Pacific white shrimp, offering new insights into aquaculture.